Comparison of Thrombophilia Assay Results for the International Society on Thrombosis and Haemostasis Scientific and Standardization Committee Plasma Standard from Different External Quality Assessment Providers—for the External Quality Assurance in Thrombosis and Haemostasis Group - Jennings, Ian; Meijer, Piet; Arunachalam, Sandya; Marlar, Richard A.; Olson, John D.; Zantek, Nicole D.; Bon, Chantal; Dean, Elysse; Hollestelle, Martine J.; Meley, Roland; Plumhoff, Elizabeth A.; Reilly-Stitt, Christopher; Salazar, Eric; Smock, Kristi J.; Spannagl, Michael; Walker, Isobel D. (Seminars in Thrombosis and Hemostasis, 2024)
External quality assessment (EQA) is used to evaluate laboratory performance in tests of hemostasis; however, some esoteric tests are performed by too few centers in any one EQA program to allow valid statistical assessment. To explore the feasibility of pooling data from several EQA providers, an exercise was carried out by the External Quality Assurance in Thrombosis and Haemostasis group, using the International Society on Thrombosis and Haemostasis Scientific and Standardization Committee (SSC) plasma standard for thrombophilia screening assays. Six EQA providers took part in this exercise, distributing the SSC plasma standard as a “blinded” sample to participants for thrombophilia tests between November 2020 and December 2021. Data were collected by each provider, anonymized, and pooled for analysis. Results were analyzed as overall results from each EQA provider, and by kit/method-specific comparisons of data from all providers pooled together. For each parameter, median results and range were determined. Over 1,250 sets of data were returned in the six EQA programs. The overall medians (all data pooled) were <4% of the assigned values for each parameter with the exception of protein C activity by clot-based assay. Method-related differences in median results were observed for free protein S antigen and protein S activity—a pattern seen across data from the different EQA providers. Antithrombin antigen results reported in mg/dL provided an example where small numbers of results for a single EQA provider may be supplemented by pooling data from multiple providers with good agreement seen among results reported by the different EQA providers. This study demonstrated that a multicenter EQA provider collaboration can be carried out and demonstrated benefit for assays with smaller number of participants. In addition, results showed good agreement with the assigned values of the SSC plasma standard. Further exercises for tests performed by only small numbers of laboratories can be planned.
Keywords: quality assurance; thrombophilia; proficiency testing